Sistematización de la experiencia de la creación, evolución y consolidación del programa de especialización en Medicina Familiar de la Universidad de La Sabana (2025)
Family Medicine is an essential discipline for comprehensive health care, focused on clinical management, prevention, and community engagement. In Colombia, it became consolidated as a medical specialty starting in 1984, and the program at Universidad de La Sabana began in 2006.